The Effectiveness of Teaching Writing Descriptive Text by Using Social Media â€œInstagramâ€ to Improve Students' Writing Ability at Junior High School Students - Encik Gayiani Warda; Armeria Wijaya (English Department FKIP Universitas Muhammadiyah Surabaya Indonesia, 2019)
Teaching writing is one skill that is taught by English teacher in school. It became important skill that student have to master writing skill. The researcher chooses Descriptive Text, because it is one of type text to describe something such as place, animal, people and things. The researcher use social media of â€œInstagramâ€ to teach student in writing descriptive text to improve students writing ability. The researcher use experimental research in quantitative method which two classes as experimental and control group. The sample of the data is taken from Barunawati Junior High School students.Â The researcher use snowball sampling. The result has been calculated by using SPSS 20.0. The result showed that teaching writing descriptive text using social mediaâ€œInstagramâ€ to improve students writing ability is effective.